Exploring Patterns of Relationship Between Trauma Symptomization and Family Constellation: Implications for Working With Trauma Presentations in Systemic Practice. Issue 4 (8th August 2017) - Gatfield, Emma; Ho, Raymond
ABSTRACT: This paper presents findings from research investigating trauma symptomization in children with prior trauma experiences from intact families (n = 32) compared with those from non-intact families (n = 32). Using a mixed method approach, a file audit of an Australian child/youth mental health service database was undertaken. Statistical analysis identified a significant relationship (p = < 0.05) of high numbers of trauma symptoms (NTS) for children from non-intact families, and low NTS for children from intact families. This finding indicates that children from intact families manage trauma better in terms of reduced symptomization. Other key patterns of relationship were identified and implications for systemic practice explored.